Mitologi dalam Perkawinan Adat Suku Jawa dengan Suku Sunda - Auliah Ambarwati; Fandy Kusuma Faizal (Jurnal Litigasi Amsir, 2022)
This study aims to determine the extent to which the mythological truth about the prohibition of marriage between the Sundanese and the Javanese. The method used is a juridical normative research, with a conceptual approach. The results of the study show that the discourse or myth regarding the Sundanese people who are not allowed to marry the Javanese is a historical story that has become multi-interpreted. Do not let us be consumed by issues that are not clear, so that it will damage the future of the nation's next generation. It needs to be instilled in each other's identity in accordance with the motto of our country which means that even though they are different, they are still one. Matters of mate, death and sustenance are divine secrets. It is the will of God who created this Universe.